Detection of Possible Resistance Mechanisms in Uropathogenic Escherichia coli Strains Isolated from Kidney Transplant Recipients Based on Whole Genome Sequencing - Soraya Herrera-Espejo; Alejandro Rubio; Lucía Ceballos-Romero; Jerónimo Pachón; Elisa Cordero; Antonio J. Pérez-Pulido; María Eugenia Pachón-Ibáñez (Biomolecules)
Background: Urinary tract infections are a global health concern, with uropathogenic Escherichia coli (UPEC) accounting for 80–90% of cases. Given the rise in antimicrobial resistance, our aim was to elucidate the genetic mechanisms behind low-level resistance to ciprofloxacin and fosfomycin (LLCR and LLFR) in UPEC strains, using whole-genome sequencing (WGS) to identify point mutations in chromosomal and plasmid genes. Methods: A cohort UPEC was collected from kidney transplant recipients at the Virgen del Rocío University Hospital, Spain. Minimum inhibitory concentrations were determined for ciprofloxacin and fosfomycin to categorize strains into LLCR and LLFR. Twenty strains were selected for WGS, with genome annotations. Point mutations were identified and analyzed using alignment tools, and protein stability changes were predicted. Results: LLCR strains exhibited mutations in key quinolone resistance-determining regions of the gyrA gene, in 83% of cases. The qnrS1 plasmid gene was found in 17% of LLCR strains. LLFR strains showed mutations in the glpT and cyaA genes. Mutations in the uhp gene family were linked to the fosfomycin-resistant phenotype, suggesting a multi-step resistance evolution mechanism. Conclusions: This study highlights the complex interplay between chromosomal and plasmid genes in UPEC’s resistance to ciprofloxacin and fosfomycin. The findings contribute to understanding low-level resistance mechanisms and may guide the development of novel therapeutic strategies to combat multidrug-resistant strains.